Facile Synthesis of Halogen Decorated para-/meta-Hydroxybenzoates by Iridium-Catalyzed Borylation and Oxidation - Shahzadi, Tayyaba; Saleem, Rahman S. Z.; Chotana, Ghayoor A. (Synthesis, 2018)
Hydroxybenzoates are an important class of phenols that are widely used as preservatives and antiseptics in the food and pharmaceutical industries. In this report, a facile preparation of 2,6- and 2,3-disubstituted 4/5-hydroxybenzoates by iridium-catalyzed borylation of respective disubstituted benzoate esters followed by oxidation is described. This synthetic route allows for the incorporation of halogens in the final hydroxybenzoates with substitution patterns not readily accessible by the traditional routes of aromatic functionalization.
Keywords: iridium-catalyzed C–H borylation; oxidation; Oxone®; hydroxybenzoates; parabens; preservatives; halogen; trifluoromethyl